Moderasi Islam dalam Pendidikan Pondok Pesantren (Studi pada Pondok Pesantren El-Bayan Kecamatan Majenang Kabupaten Cilacap) - Falak, Imron (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This study tries to explain the practice of Islamic moderation at the El-Bayan Islamic Boarding School. This is done as a form of support for the realization of moderate individuals and society, given the diversity and diversity that has always been maintained and preserved in Indonesia, recently tested by the emergence of social conflicts. Starting from cases of religious blasphemy, destruction of houses of worship, hate speech on social media and mutual discredit between one community and another. This research is part of a qualitative research with field research, collecting data through unstructured interviews and documentation. After the data is collected, it is processed and conclusions are drawn using a induktif method. The theory used is the theory of habitus. The results of this study indicate that Islamic boarding schools, especially the El-Bayan Islamic boarding school, teach, educate and familiarize (habituation) students with moderate values in the form of activities carried out, including attending formal (religious) and non-formal (general) education so that have universal insight, sufficient rest and sports entertainment activities so that they can think and learn to focus, apply sanctions to anyone who violates indiscriminately, respect each other in both learning and other activities, deliberations in solving problems and others. The refraction of these activities is expected to form students who have moderate attitudes, not extreme left (conservative) or extreme right (liberal), so that they can become role models in religious moderation.